EXPERIMENTAL STUDY OF CONTINUOUS ELECTROCOAGULATION TREATMENT OF PEAT WATER IN SARAWAK WITH ALUMINIUM ELECTRODE - ALLENE ALBANIA, LINUS (Universiti Malaysia Sarawak (UNIMAS), 2018)
Sarawak is the largest state in Malaysia with a total area of peat land of about 2.6Mha that contribute 70% of Malaysia’s total peat land. The state government is currently looking forward for the implementation of the Sarawak Alternative Rural Water Supply (Sawas) programme with purpose of providing safe and clean water to rural areas. The programme is aimed to provide clean water to about 114,000 households in the rural areas. The increasing demand of clean water and also the ageing reticulation system contributed to the low water supply especially in many rural and coastal areas. The state government also aims to look into non-revenue water programme. Since, peat land is abundance in Sarawak especially the coastal areas, the utilization of naturally found peat water is an alternative. Peat water can be associated with red-brownish colour with high humic substances contain. Thus, treatment of peat water is essential before fully utilization as clean water. Therefore, the study main aim is to develop an electrocoagulation process for treatment of peat water of rural coastal region of Sarawak with Aluminium electrodes. The focus is on the treatment of peat water in the rural coastal area of Sarawak. The model for electrocoagulation treatment system is built with materials and technology available locally. In addition, the fabrication and maintenance processes must be simple and easy. The study is conducted in the form of literature review, sampling and data analysis, design and fabrication of system and data analysis focusing on the most sustainable system for electrocoagulation as a treatment system for peat water. The continuous electrocoagulation reactor is fabricated and experimental studies in conducted on electrode distance, number of plates, treatment time and current density. Several parameters are investigated such as COD, TOC, colour, turbidity, heavy metal and pH. The developed electrocoagulation treatment system is able to remove the parameters to meet Ministry of Health Standard except for colour which is slightly higher. This is due to improper filtration system used. Last but not least, the continuous electrocoagulation treatment system is feasible with the most optimized condition of 0.5 cm Aluminium electrode spacing, 20 plates, 21 A/m2 and treatment time of 25 minutes.